(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
We talk about the recently presented idea of cone metric spaces. We additionally examine the fixed point presence results of contractive mappings characterized on such metric spaces. Specifically, we demonstrate that a large portion of the new results are just duplicates of the established ones. In this paper we set up some Fixed Point theorems by altering distances in a complete cone metric space with supposition that the cone is normal, likewise we present MS-Altering function.